Analyzing Blockchain Adoption for Copyright Certification in Lombok's Woven Industry: An Extended TAM Perspective - Bimantari, Joselina Rizki; Wijayanto, Heri; Widiartha, Ida Bagus Ketut; Afwani, Royana (Informatika, Universitas Jenderal Soedirman, 2025)
This research explores the Extended Technology Acceptance Model (TAM) and Partial Least Squares Structural Equation Modelling (PLS-SEM) to investigate the acceptability of blockchain-based digital copyright certification among traditional woven fabric SMEs (Small and Medium Enterprises) in Lombok. This research develops a blockchain-based certification system using NFTs, IPFS, and ECDSA to secure ownership, metadata, and authentication of traditional woven fabrics in Lombok. The problem addressed is the lack of understanding and acceptance of blockchain technology for copyright certification among SMEs, which can impede the protection of their innovations. The aim of this study is to analyze the variables that influence this technology's acceptance and to provide strategies for increasing its adoption. This study explores blockchain-based copyright certification adoption among Lombok's woven fabric SMEs using an Extended TAM with novel variables: Perceived Trust, Privacy, and Government Regulations. Findings from PLS-SEM reveal these, alongside traditional TAM factors, significantly impact adoption. By addressing digital literacy gaps and regulatory challenges, this research provides insights into promoting blockchain adoption through targeted training and outreach, contributing to innovation protection for traditional artisans. A quantitative method was implemented with a validated and reliable surveys distributed both online and offline to SMEs in three main woven villages in Lombok. Data analysis using PLS-SEM revealed significant impacts of perceived usefulness (PU), perceived ease of use (PEOU), Perceived Trust (PT), Government Regulations (GR), Perceived Protection (PP), attitude towards using (ATU), and behavioral intention to use (BITU) on the acceptance of blockchain technology. This study concludes that TAM factors are crucial in evaluating these SMEs' acceptance of blockchain-based copyright certification. Recommendations are provided to enhance SMEs understanding and skills in applying this technology through targeted training and outreach.